Social Networks and Their Role in Development of Civic Activity of the Ukrainian Youth - Tatiana Savrasova-V’un (Communication Today, 2025)
The research article aims to describe the overall strategy of the experimental studies aiming to provide a thorough set of knowledge on social networks’ influence on the level of development of the Ukrainian youth’s civic activity. The author presents the results of her own theoretical and research reflection on the structure and characteristics of the civic activity associated with the Ukrainian youth. The proposed criteria, indicators and diagnostic techniques have led to an empirical research on the Ukrainian youth’s civic activity and its specifics. Firstly, the article refers to various theories and research materials by renowned scholars that reflect on the issue of social networking (social networks, their objectives and functioning in the online space, their impact on the personal development). Secondly, the research study aims to define and discuss the features of the social networks’ influence on the Ukrainian youth’s civic activity and its further development. The author also offers an overview of the level of the Ukrainian youth’s civic activity that, as the presented research results reveal, is high in case of the majority of the research participants. The issues related to the use of social networks by young Ukrainian people, i.e. the facts that explain their attitude to this form of communication are also addressed thoroughly, as well as the need for defining the role of social networks in the process of education. The results of the included correlation analysis suggest that the level of the Ukrainian young people’s civic activity and its further development are directly dependent on the use of online social networks. Many young Ukrainians who regularly use social networks are highly active in terms of the civic matters. The research results may help to effectively organise and implement various society-wide projects that would be aimed at the young people in Ukraine specifically.